2021
DOI: 10.1007/s11325-021-02364-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety and hemodynamic, cardiac autonomic and inflammatory responses to a single session of inspiratory muscle training in obstructive sleep apnea

Abstract: Purpose To determine clinical safety and cardiovascular, cardiac autonomic and inflammatory responses to a single session of inspiratory muscle training (IMT) in obstructive sleep apnea (OSA) subjects. Methods In a randomized controlled trial individuals of both sexes, aged between 30 and 70 years old with diagnosis of moderate to severe OSA were enrolled. Volunteers with OSA (n = 40) performed an IMT session with three sets of 30 repetitions with a 1-min interval between them. The IMT group (n = 20) used a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The smallest studies included 16 adult participants (Nóbrega‐Júnior et al, 2020; Souza et al, 2018) and the largest study included 55 participants (Moawd et al, 2020). Five RCTs evaluated individuals who were not using CPAP (Erturk et al, 2020; Ferreira et al, 2022; Kuo et al, 2017; Souza et al, 2018; Vranish & Bailey, 2016), two assessed participants using equipment or other assistive devices (Ramos‐Barrera et al, 2020; Vivodtzev et al, 2018), and the others did not report. The studies included participants with varying levels of disease severity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smallest studies included 16 adult participants (Nóbrega‐Júnior et al, 2020; Souza et al, 2018) and the largest study included 55 participants (Moawd et al, 2020). Five RCTs evaluated individuals who were not using CPAP (Erturk et al, 2020; Ferreira et al, 2022; Kuo et al, 2017; Souza et al, 2018; Vranish & Bailey, 2016), two assessed participants using equipment or other assistive devices (Ramos‐Barrera et al, 2020; Vivodtzev et al, 2018), and the others did not report. The studies included participants with varying levels of disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included participants with varying levels of disease severity. The intervention duration of the included studies ranged from very short term (up to 1 month; Ferreira et al, 2022) to short term (up to 12 weeks; Azeredo et al, 2019; Erturk et al, 2020; Fischer et al, 2019; Kuo et al, 2017; Labeix et al, 2022; Lin, Chang, et al, 2020; Moawd et al, 2020; Nóbrega‐Júnior et al, 2020; Ramos‐Barrera et al, 2020; Souza et al, 2018; Vivodtzev et al, 2018; Vranish & Bailey, 2016). No study reported an intervention time longer than 12 weeks (medium and long term).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 studies included five trials (Table 1 ) focusing on healthy adults, 8 , 17 , 18 , 19 , 20 five trials focusing on patients with hypertension (simple systolic hypertension, 21 , 22 , 23 Grade I and II hypertension 24 and essential hypertension 16 ) and two tests on patients with OSA 25 , 26 from five countries including the USA, China, Brazil, Thailand, and Turkey. A total of 386 participants were enrolled in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 articles included in this paper (Table 2 ), nine studies 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 used threshold devices and three studies 21 , 23 , 24 used flow resistance loads with MIP ranging from 15% to 75% of MIP and water column fluctuations in the range of 18−20 mm H 2 O. There are two studies 18 , 20 in which several groups of different resistances were compared.…”
Section: Resultsmentioning
confidence: 99%